Improved elevated temperature performance of Al-intercalated V2O5 electrospun nanofibers for lithium-ion batteries - Cheah, Yan Ling (2012)
Al-inserted vanadium pentoxide (V2O5) nanofibers (Al-VNF) are synthesized by simple electrospinning technique. Powder X-ray diffraction (XRD) patterns confirm the formation of phase-pure structure. Elemental mapping and XPS studies are used to confirm chemical insertion of Al in VNF. Surface morphological features of as-spun and sintered fibers with Al-insertion are investigated by field emission scanning electron microscopy (FE-SEM). Electrochemical Li-insertion behavior of Al-VNFs are explored as cathode in half-cell configuration (vs. Li) using cyclic voltammetry and galvanostatic charge-discharge studies. Al-VNF (Al0.5V2O5) shows an initial discharge capacity of ~250 mAh g–1 and improved capacity retention of >60% after 50 cycles at 0.1 C rate, whereas native VNF showed only ~40% capacity retention at room temperature. Enhanced high current rate and elevated temperature performance of Al-VNF (Al1.0V2O5) is observed with improved capacity retention (~70%) characteristics. Improved performance of Al-inserted VNF is mainly attributed to the retention of fibrous morphology, apart from structural stabilization during electrochemical cycling.